Liquid phase alkylation of phenol with 1-octene over large pore zeolites - Wagholikar, Smita; Mayadevi, S.; Sivasanker, S. (Applied Catalysis A-General, 2006)
A comparative study is presented of the liquid phase alkylation of phenol with 1-octene over different zeolite catalysts: H-beta (BEA(15)), H-mordenite (MOR(11)) and H-USY (FAU(15)). A wide spectrum of monoalkylated products, identified as isomers of phenyl octyl ether (O-alkylate) and octyl phenol (C-alkylate), was formed in the reaction. The reaction was studied in detail over BEA(15), such studies included the influence of process variables such as temperature, reactant mole ratio, catalyst amount and alkali metal (K) poisoning on its performance in the alkylation reaction. A kinetic analysis of the reaction over BEA(15) was also carried out assuming a second order parallel reaction mechanism. The activity of the different catalysts for the reaction followed the order: BEA(15) > FAU(15) > MOR(11). The poisoning of BEA(15) with potassium resulted in a decrease in the catalyst activity concomitant with a decrease in the number of strong acid centres in the catalyst. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 1-octene; alkyl phenols; Alkylation; phenol; zeolites